CRISP1 as a novel CatSper regulator that modulates sperm motility and orientation during fertilization - Ernesto, Juan I. (J Cell Biol, 2015)
Ca(2+)-dependent mechanisms are critical for successful completion of fertilization. Here, we demonstrate that CRISP1, a sperm protein involved in mammalian fertilization, is also present in the female gamete and capable of modulating key sperm Ca(2+) channels. Specifically, we show that CRISP1 is expressed by the cumulus cells that surround the egg and that fertilization of cumulus–oocyte complexes from CRISP1 knockout females is impaired because of a failure of sperm to penetrate the cumulus. We provide evidence that CRISP1 stimulates sperm orientation by modulating sperm hyperactivation, a vigorous motility required for penetration of the egg vestments. Moreover, patch clamping of sperm revealed that CRISP1 has the ability to regulate CatSper, the principal sperm Ca(2+) channel involved in hyperactivation and essential for fertility. Given the critical role of Ca(2+) for sperm motility, we propose a novel CRISP1-mediated fine-tuning mechanism to regulate sperm hyperactivation and orientation for successful penetration of the cumulus during fertilization.